2012
DOI: 10.1097/mcg.0b013e31824432cb
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound Guided Fine-needle Aspiration of Lymph Nodes and Solid Masses

Abstract: EUS-guided FNA obtains a high proportion of adequate aspirates for LNs and solid masses, even without an on-site cytopathologist. Small proportions of inadequate samples still occur. For solid masses, a 25-G needle with at least 3 passes is more likely to provide an adequate aspirate than a 22-G needle and fewer passes. Hemorrhage did not affect the cytopathology's ability to make a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…A further study demonstrated equivalency of 25 G needles and 22 G needles in lymph node biopsies, a nonsignificant advantage of 25 G needles in solid pancreatic lesions and a non-significant advantage of 22 G needles in SETs [494]. This agrees with two studies showing similar diagnostic yields for 22 G needles and 25 G needles for EUS-FNA of various nonpancreatic lesions and lymph nodes, but a higher yield of the 25 G aspiration needle for pancreatic lesions [291,499]. In conclusion, the advantage of the 25 G needle appears to be limited to pancreatic lesions, in particular within the pancreatic head.…”
Section: G Vs 25 G Aspiration Needlessupporting
confidence: 82%
“…A further study demonstrated equivalency of 25 G needles and 22 G needles in lymph node biopsies, a nonsignificant advantage of 25 G needles in solid pancreatic lesions and a non-significant advantage of 22 G needles in SETs [494]. This agrees with two studies showing similar diagnostic yields for 22 G needles and 25 G needles for EUS-FNA of various nonpancreatic lesions and lymph nodes, but a higher yield of the 25 G aspiration needle for pancreatic lesions [291,499]. In conclusion, the advantage of the 25 G needle appears to be limited to pancreatic lesions, in particular within the pancreatic head.…”
Section: G Vs 25 G Aspiration Needlessupporting
confidence: 82%
“…3 Cellularity was assessed by using a 4-point scale (0 Z no cells, 1 Z sparsely cellular, 2 Z moderately cellular, 3 Z highly cellular). Blood contamination was graded on a 3-point scale (0 Z free of blood, 1 Z contaminated with red blood cells, 2 Z blood clots present).…”
Section: Cytopathological Assessmentmentioning
confidence: 99%
“…[39] As a function of the study and categorization of “suspicious” result, diagnostic samples are reported in 91-100% of performed procedures. [8404142] While the presence of a pathologist on site may improve sample adequacy in a retrospective study,[40] no correlation between LN characteristics and cellularity of samples was reported.…”
Section: Performance Of Eus-fna According Type Of Pathologymentioning
confidence: 99%